Perceptions towards childhood asthma and barriers to its management among patients, caregivers and healthcare providers: a qualitative study from Ethiopia - Eden Kassa; Rahel Argaw Kebede; Bruck Messele Habte (BMC Pulmonary Medicine, 2022)
Abstract Background The management of asthma, which is one of the major causes of childhood morbidity and mortality has been affected by non-adherence to recommended treatment regimens with severe consequences. The aim of the present study was therefore to explore the perceptions of the children with asthma, their caregivers and their healthcare providers towards asthma and barriers to long term childhood asthma management in an institutional setting in Addis Ababa, Ethiopia. Methods A qualitative descriptive design was followed for the present study that used individual interviews as a data collection method. The study participants were 23 pairs of children with asthma that had treatment follow-ups in two tertiary hospitals and their caregivers and eight healthcare providers who cared for these children. The data was analyzed using thematic analysis approach. Results The study findings revealed that the children’s reported adherence to the recommended treatment regimens was low and they along with their caregivers were facing physical, emotional and social burdens related to asthma. Some of the influencing factors affecting childhood asthma management were found to be the low-level implementation of the asthma management guidelines by the healthcare providers, limited awareness about asthma and its management by the children and their caregivers, use of traditional home remedies and religious healing on a complementary and alternative basis and inadequate education received from healthcare professionals. Further identified barriers to the adherence of especially inhaled corticosteroids appear to be the low necessity beliefs towards chronic administration of treatment regimens and concerns related with difficulty of administration, fear of side effects and general negative attitude towards it, in addition to their low availability and affordability. Conclusions Low awareness of the biomedical treatment regimens and use of traditional home remedies and religious healing by the children with asthma and their caregivers, the low-level implementation of the asthma management guidelines as well as low access to medications may among other things contribute to the low adherence of the children to their recommended regimens. The findings support the need for implementation of asthma management guidelines, institution of strong asthma care and education programs that are sensitive to local and individual patients’ and caregiver perceptions and experiences including emotional distress, the need to institute chronic care approach and ways to address patients’ medication access issues.